Investigation Impact Literacy Finance and Socialization Financial to Satisfaction Finance Through Attitude Risk Finance: Perspective Generation Millennials - Nurhaeni, Nurhaeni; Digdowiseiso, Kumba (Universitas Muhammadiyah Yogyakarta, 2024)
This study investigates financial literacy and socialization's impact on financial satisfaction through financial risk attitudes. The researchers collected data from 240 respondents aged 24–39 through a web-based self-administered questionnaire. The data were analyzed using Structural Equation Modeling (SEM) with Stata 14 for hypothesis testing. The results showed that financial literacy positively and significantly affected financial satisfaction. In contrast, financial socialization had no significant impact on financial satisfaction. Financial risk attitudes had a significant positive effect, facilitating the relationship between financial literacy and financial satisfaction. Financial risk attitudes also significantly impacted the moderating of financial literacy and financial socialization on financial satisfaction. The findings of this study contribute to the literature on financial satisfaction and encourage the successful delivery of financial services to the millennial generation, followed by recommendations for providing financial literacy for individuals. The results of this study can also be a reference for public policy development.